Improvement in Brightness Uniformity by Compensating for the Threshold Voltages of Both the Driving Thin-Film Transistor and the Organic Light-Emitting Diode for Active-Matrix Organic Light-Emitting Diode Displays - Ching-Lin Fan; Hao-Wei Chen; Hui-Lung Lai; Bo-Liang Guo; Bohr-Ran Huang (International Journal of Photoenergy)
This paper proposes a novel pixel circuit design and driving method for active-matrix organic light-emitting diode (AM-OLED) displays that use low-temperature polycrystalline-silicon thin-film transistors (LTPS-TFTs) as driving element. The automatic integrated circuit modeling simulation program with integrated circuit emphasis (AIM-SPICE) simulator was used to verify that the proposed pixel circuit, which comprises five transistors and one capacitor, can supply uniform output current. The voltage programming method of the proposed pixel circuit comprises three periods: reset, compensation with data input, and emission periods. The simulated results reflected excellent performance. For instance, when ΔVTH=±0.33 V, the average error rate of the OLED current variation was low (<0.8%), and when ΔVTH_OLED=+0.33 V, the error rate of the OLED current variation was 4.7%. Moreover, when the I×R (current × resistance) drop voltage of a power line was 0.3 V, the error rate of the OLED current variation was 5.8%. The simulated results indicated that the proposed pixel circuit exhibits high immunity to the threshold voltage deviation of both the driving poly-Si TFTs and OLEDs, and simultaneously compensates for the I×R drop voltage of a power line.